Pharmacokinetics in Zebrafish Embryos (ZFE) Following Immersion and Intrayolk Administration: A Fluorescence-Based Analysis - Marlly Guarin; Annelii Ny; Noémie De Croze; Jan Maes; Marc Léonard; Pieter Annaert; Peter A. M. de Witte (MDPI AG, 2021)
Zebrafish embryos (ZFE) have increasingly gained in popularity as a model to perform safety screenings of compounds. Although immersion of ZFE is the main route of exposure used, evidence shows that not all small molecules are equally absorbed, possibly resulting in false-negative readouts and incorrect conclusions. In this study, we compared the pharmacokinetics of seven fluorescent compounds with known physicochemical properties that were administered to two-cell stage embryos by immersion or by IY microinjection. Absorption and distribution of the dyes were followed at various timepoints up to 120 hpf by spatiotemporal fluorescence imaging. The concentration (10 µM) and dose (2 mg/kg) used were selected as quantities typically applied in preclinical experiments and zebrafish studies. The data show that in the case of a lipophilic compound (log D: 1.73) the immersion procedure resulted in an intrabody exposure which is similar or higher than that seen after the IY microinjection. In contrast, zero to low intrabody exposure was reached after immersion of the embryos with less lipophilic compounds. In the latter case IY microinjection, a technical procedure that can be easily automated, is highly recommended.